2014
DOI: 10.5455/msm.2014.26.129-133
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Genotypes in Iran

Abstract: Hepatitis B virus (HBV) infection is a public health problem as a cause of liver diseases including hepatocellular carcinoma and cirrhosis. It is estimated that 350 million people live with chronic infection and about one million people die every year from complication of this chronic disease in the world. So far, ten HBV genotypes (A-J) has been identified which show a geographical distribution. Throughout the world, carrier variability rate for hepatitis B infection is estimated to be 0.1% to 20%, with regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
(38 reference statements)
3
23
0
Order By: Relevance
“…Several studies in Iran have shown that genotype D is the only genotype observed in different parts of the country (29). However, genotype B was reported in a case in Kermanshah Province, which is located in western Iran (22).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Iran have shown that genotype D is the only genotype observed in different parts of the country (29). However, genotype B was reported in a case in Kermanshah Province, which is located in western Iran (22).…”
Section: Discussionmentioning
confidence: 99%
“…A rise in general public awareness about HBV transmission, along with the mass vaccination program in place since 1993 for all neonates, healthcare workers, and others at risk of HBV infection, has influenced the outcome of this disease (10). The results of epidemiological studies in Iran showed that the predominant genotype and serotype of HBV are D and ayw2, respectively (11). The most common routes of HBV transmission in Iran are perinatal transmission and intravenous drug abuse; however, during recent years, the epidemiology of this infection is changing from a vertical to a horizontal route (12).…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Accordingly, the participants are living in a region with intermediate endemicity for HBV infection. However, none of the subjects of the present study were positive for HBsAg, anti-HBc antibodies or reported to have clinical symptoms of HBV infection during the 20 years after primary HB vaccination.…”
Section: 21mentioning
confidence: 99%